'The school with the Bible': From meaningless to meaningful Citizenship Education in South Africa - S. Schoeman (Koers : Bulletin for Christian Scholarship, 2002)
Citizenship Education has re-emerged as an important issue in Curriculum 2005. Closer scrutiny of this educational innovation reveals the existence of a number of problems. The aim of this article is, on the one hand, to sensitise policy-makers, curriculum developers and educational administrators who are involved in the drafting of a blueprint for Citizenship Education in public schools, to the need to take note of Reformational Christians’ views on government, citizenship and society, and the quest for the socalled “school with the Bible”; and on the other, to assist Reformational Christian educators responsible for the teaching of Citizenship Education in public schools to teach it from a biblical perspective. To this end, this article intends the following: to explore some tenets of a Reformational Christian theology of state (like John Calvin’s); to revisit the Reformational Christian doctrine of sphere sovereignty; and illustrate the practical implementation of Calvin’s theology of state and the Reformational Christian doctrine of sphere sovereignty in Citizenship Education teaching in public schools.